SOSIALISASI PENDAFTARAN TANAH SISTEMATIK LENGKAP (PTSL) DI DESA BOKORI KECAMATAN SOROPIA KABUPATEN KONAWE - Heryanti Heryanti; Nur Intan; Sahrina Safiuddin; Jumiati Ukkas; Rizal Muchtasar; Ramadan Tabiu; St. Muslimah Suciati; Muh. Nazzar (Universitas Halu Oleo, 2023)
The outreach activity aims to ensure that the public understands the urgency and process of land registration so that it can raise public legal awareness in registering their land, especially through the Complete Systematic Land Registration (PTSL) program. Preparation for socialization activities is carried out starting from determining the location to identifying legal problems in the community, then preparing socialization materials. The activity was carried out using the method of delivering socialization material to participants which was then followed by questions and answers. The activity was carried out by the community service team from the university involving students. The results of the activity were that one of the things that reduced people's interest in certifying their land was the registration procedure which felt complicated and land registration fees which were felt to be still expensive, especially if registration was carried out sporadically. The PTSL program is considered to really help the community to be able to certify their land because the government plays an active role in carrying out data collection activities on community land that has not been certified so that mass land registration can then be carried out in a village/sub-district area and the government, especially the regional government, can also help in financing the certificate processing.